Indonesia : 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report ;, 2009)
Indonesia entered the current global crisis with strong initial conditions. This 2009 Article IV Consultation highlights that notwithstanding the initial impact of the global crisis, the economy has rebounded in 2009. Macroeconomic policy responses have kept appropriate pace with the evolving economic conditions. Executive Directors have welcomed the resilience of the Indonesian economy, which owed much to strong initial fundamentals and appropriate policy responses. The financial sector has recovered from the adverse initial impact of the global turmoil, and investor sentiment has improved in recent months.